2011
DOI: 10.1007/s10578-011-0223-8
|View full text |Cite
|
Sign up to set email alerts
|

Links Between Maternal and Child Psychopathology Symptoms: Mediation Through Child Emotion Regulation and Moderation Through Maternal Behavior

Abstract: This study examined the intergenerational transmission of psychopathology symptoms with 7-12 year-old children (N = 97; 44 boys, 53 girls, M age = 9.14, SD = 1.38) and their mothers (M age = 38.46, SD = 6.86). Child emotion regulation mediated the links between maternal psychopathology and child internalizing and externalizing symptoms. In turn, the indirect effect was dependent on the level of maternal support in response to youth's expressions of negative emotions when considering particular constellations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 59 publications
(73 reference statements)
9
62
1
1
Order By: Relevance
“…Maternal and paternal depression has been shown to have deleterious and long-lasting effects on a child's cognitive and socio-emotional development [21][22][23][24]. Other mental health problems of the parent have also been shown to relate to child maladjustment, [25,26]. Increased parenting stress may also be an important risk factor for child development.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal and paternal depression has been shown to have deleterious and long-lasting effects on a child's cognitive and socio-emotional development [21][22][23][24]. Other mental health problems of the parent have also been shown to relate to child maladjustment, [25,26]. Increased parenting stress may also be an important risk factor for child development.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the findings of this study coincide with longitudinal studies that have found contingent reactions and mother-child discussions are less impactful as children enter the early or late elementary stages (Denham et al, 1991;Gentzler et al, 2005). Interestingly, cross-sectional research with late elementaryaged children continues to support the association between parents' contingent reactions and children's EC (Gentzler et al, 2005;Shaffer et al, 2012;Suveg et al, 2011); however, these prior studies were conducted with families of TD children, whereas the current study had a sample in which half of the children met criteria for ADHD.…”
Section: Theoretical Implicationssupporting
confidence: 84%
“…The association between nonsupportive contingent reactions and children's' more intense negative emotional expressivity is likely driven by their poorer regulatory skills. Indeed, several studies have found a negative association between nonsupportive contingent reactions and parent-ratings of preschool (Perry et al, 2011) and late elementary-aged (Gentzler et al, 2005;Shaffer et al, 2012;Suveg, Shaffer, Morelen, & Thomassin, 2011) children's emotional coping and regulation. However, all of these studies have been primarily based on parent-report of contingent reactions and children's emotion regulation; thus, it is possible that this link is a reflection of parents' general negative perspective of the child's behavior.…”
Section: Contingent Reactions To Children's Emotions In Td Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptom dimensions (internalizing vs. externalizing behaviors) and the individual forms of psychopathology examined (e.g., anxiety) may all be important determinants of whether parental emotion socialization behaviors-especially those that are often considered non-supportive (i.e., punitive and minimization reactions)-are associated with adaptive or maladaptive outcomes. Suveg and colleagues found that the association between parental minimization, punitive, and distress reactions and child psychopathology was significant for externalizing symptoms but not for internalizing symptoms (Suveg et al 2011). Moreover, the association between child emotion regulation difficulties and internalizing psychopathology was only significant in the context of low levels of unsupportive parenting reactions (i.e., less minimization, punitive, and distress reactions).…”
Section: Parental Emotion Socialization and Child Interpretation Biasesmentioning
confidence: 99%